Movement disorders after hypoxic brain injury following cardiac arrest in adults. (26th June 2020) - Scheibe, F.; Neumann, W. J.; Lange, C.; Scheel, M.; Furth, C.; Köhnlein, M.; Mergenthaler, P.; Schultze‐Amberger, J.; Triebkorn, P.; Ritter, P.; Kühn, A. A.; Meisel, A.
Abstract : Background and purpose: Post‐hypoxic movement disorders and chronic post‐hypoxic myoclonus are rare complications after cardiac arrest in adults. Our study investigates the clinical spectrum, neuroimaging results, therapy and prognosis of these debilitating post‐hypoxic sequelae. Methods: This retrospective study included 72 patients from the neurological intensive care unit at a university hospital, who were diagnosed with hypoxic‐ischaemic encephalopathy after cardiac arrest between January 2007 and September 2018. Clinical records were screened for occurrence of post‐hypoxic movement disorders and chronic post‐hypoxic myoclonus. Affected patients were further analysed for applied neuroprognostic tests, administered therapy and treatment response, and the outcome of these movement disorders and neurological function. Results: Nineteen out of 72 screened patients exhibited post‐hypoxic motor symptoms. Basal ganglia injury was the most likely neuroanatomical correlate of movement disorders as indicated by T1 hyperintensities and hypometabolism of this region in magnetic resonance imaging and positron emission tomography computed tomography. Levomepromazine and intrathecal baclofen showed first promising and mostly prompt responses to control these post‐hypoxic movement disorders and even hyperkinetic storms. In contrast, chronic post‐hypoxic myoclonus best responded to co‐application of clonazepam, levetiracetam and primidone. Remission rates of post‐hypoxic movement disorders and chronic post‐hypoxic myoclonus were 58% and 50%, respectively. Affected patients seemed to present a rather good recovery of cognitive functions in contrast to the often more severe physical deficits. Conclusions: Post‐hypoxic movement disorders associated with pronounced basal ganglia dysfunction might be efficiently controlled by levomepromazine or intrathecal baclofen. Their occurrence might be an indicator for a more unfavourable, but often not devastating, neurological outcome.